1999
DOI: 10.1161/01.str.30.5.1038
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Ischemic Hyperintensity on T1-Weighted MRI in the Caudoputamen and Cerebral Cortex of Humans After Spectacular Shrinking Deficit

Abstract: Background and Purpose-Transient internal carotid artery (ICA)-middle cerebral artery (MCA) occlusion caused by cardiogenic embolus can lead to spectacular shrinking deficit (SSD): sudden hemispheric stroke syndrome followed by rapid improvement. The aim of this study was to investigate sequential neuroradiological changes in the brains of patients after SSD compared with those after brief cardiac arrest and hypoglycemia, which we previously studied with the same methods. Methods-We serially studied CT scans a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
1
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 32 publications
6
47
1
3
Order By: Relevance
“…This seems to be of special interest given the contradicting significance attributed to brief cerebral ischemia. Whereas some studies found that transient cerebral ischemia may improve stroke outcome by serving as a preconditioning stimulus that triggers neuroprotective pathways in the brain (Castillo et al, 2003;Wegener et al, 2004), others demonstrated secondary deterioration on MRI (Fujioka et al, 1999a) or neurological function (Johnston et al, 2003;Smith et al, 2005) similar to the herein observed pathology. Hence, withholding treatment in these patients should be reconsidered and more aggressive interventions may be indicated in patients with rapidly improving symptoms, who currently are often treated with little urgency or concern (Johnston et al, 2003;Smith et al, 2005).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This seems to be of special interest given the contradicting significance attributed to brief cerebral ischemia. Whereas some studies found that transient cerebral ischemia may improve stroke outcome by serving as a preconditioning stimulus that triggers neuroprotective pathways in the brain (Castillo et al, 2003;Wegener et al, 2004), others demonstrated secondary deterioration on MRI (Fujioka et al, 1999a) or neurological function (Johnston et al, 2003;Smith et al, 2005) similar to the herein observed pathology. Hence, withholding treatment in these patients should be reconsidered and more aggressive interventions may be indicated in patients with rapidly improving symptoms, who currently are often treated with little urgency or concern (Johnston et al, 2003;Smith et al, 2005).…”
Section: Discussionsupporting
confidence: 60%
“…In conclusion, this study may provide clinicians with the important information that rapid resolution of ADC lesions after embolic MCAO with spontaneous reperfusion may not be permanent, arguing against the notion that SSD is a monophasic phenomenon (Baird et al, 1995;Kraemer et al, 2005;Minematsu et al, 1992) and for a more heterogeneous event with potentially delayed ischemic sequelae (Fujioka et al, 1999a). Secondly, fMRI is capable of identifying dysfunctional tissue after embolic stroke that eludes standard structural MRI techniques, and may be a sensitive and complementary parameter in the evaluation of stroke patients with rapidly improving symptoms.…”
Section: Discussionmentioning
confidence: 84%
“…[1][2][3] However, we suggested in our clinical study that a delayed change on MRI represented incomplete ischemic injury, including selective neuronal death and gliosis without infarct or hemorrhage. 4 This ischemic change exhibited persistent hyperintensity and hypointensity on repeated T1-weighted (T1W) and T2-weighted (T2W) MRI, respectively, with the hyperintensity on T1W imaging gradually subsiding with time. Brief cerebral hemispheric ischemia leading to spectacular shrinking deficit produced the specific ischemic change in the basal ganglia and cerebral cortex in humans on MRI but not CT scans.…”
mentioning
confidence: 99%
“…Les implications de ces mécanismes dans le traitement des attaques céré-brales et les raisons de l'échec de l'utilisation des antagonistes des récepteurs NMDA dans les essais cliniques humains sont également discutées. < [4][5][6]. In vitro, après une hypoxie-aglycémie de quatre à six minutes, la mort des neurones vulnérables est constatée entre 24 et 72 h [7].…”
Section: Vulnérabilité Neuronale Et Mort Retardée Des Neuronesunclassified